Effect of plastic canopy and type of fertilizer on nitrate content and growth of spinach (Amaranthus Sp.) - Sri Endah Prasetyowati Susilaningsih (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2012)
A research on the effect of shading and fertilizer on nitrate content and the growth of spinach (Amaranthus sp) has been done at the experimental field of Agriculture Faculty, from October to November 2010. It was located in Batikan, Yogyakarta Special Territory. The study was intended to find out the effect of plastic shading and kind of fertilizer and its interaction on nitrate content and the growth of spinach. The experiment was a split plot, arranged in a completely randomized design. The main plot was shading which is consisted of two levels i.e. without shading and plastic shading. The main plots split into four different kind of fertilizers applied namely: urea, compound fertilizer NPK, manure, and compost. The result showed that the used of plastic shading gave higher nitrate content in spinach compared to open air, while plans with compost application have better growth than others.Keywords: plastic canopy, fertilizer, nitrate content, spinach,